Super‐refractory status epilepticus in West China. (14th October 2014) - Tian, L.; Li, Y.; Xue, X.; Wu, M.; Liu, F.; Hao, X.; Zhou, D.
<x xml:space="preserve">Abstract</x> Objective This study aims to determine the general frequency, mortality, and risk factors of super‐refractory status epilepticus (SRSE) versus non‐refractory status epilepticus (NRSE) and refractory status epilepticus (RSE). Methods This work is a retrospective study. Clinical data of patients who were diagnosed with status epilepticus (SE) in the neurological ward and neuro‐intensive care unit of West China Hospital from January 2009 to December 2012 were collected and analyzed. Results A total of 98 patients were included in the study. The percentages of NRSE, RSE, and SRSE were 67.3%, 20.4%, and 12.2%, respectively. Convulsive SE was the main seizure type among the three groups. The most common cause of NRSE was related to epilepsy (EP). However, 67.7% of SRSE cases were caused by acute encephalitis. Moreover, 47% of SE and 40% of RSE cases had a history of EP, whereas only 8.3% of SRSE cases had such history (P < 0.01). The percentage of patients with STESS ≤2 was lowest in the SRSE group without statistical significance (P > 0.05). The general mortality of SE was 7.1%, whereas that of SRSE was 50%. During follow‐up, most SRSE patients who survived have developed symptomatic EP. Conclusions This study was the first to use the statistical percentage of SRSE. Approximately 12.2% of SE cases will result in SRSE, which is a challenging medical situation for doctors. Patients with first episodes and acute encephalitis were also prone to develop SRSE.